Integrating Total Quality Management and Maqāṣid al-Sharīʿah under Spiritual Prestige-Driven Transformation - Taufikin Taufikin; Muhammad Shobirin; Habib Badawi (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
This study analyses how Total Quality Management (TQM) is implemented in the governance of elite Islamic boarding schools through the interaction between the Visionary, Integrated, and Prestigious (VIP) orientation and maqāṣid al-sharī'ah as an ethical control system. The study employs a qualitative approach with a multi-case study design at Pesantren Ar-Rohmah Putra Malang, IBS Ar-Rohmah Putri Malang, and Pesantren Islam Al-Irsyad Tengaran. Data were collected through document analysis, semi-structured interviews with 22 informants, and participatory observation, and were subsequently analysed using reflexive thematic analysis and cross-case comparisons. The results indicate that TQM serves as a stabilising mechanism for the quality management process through system strengthening, continuous evaluation, accountability, and evidence-based decision-making. The implementation of TQM is influenced by VIP Orientation, which reinforces strategic vision, institutional integration, and institutional legitimacy. At the same time, maqāṣid al-sharī'ah functions as an ethical control mechanism that ensures all managerial practices remain oriented toward Islamic values. The interaction of these three elements forms the Spiritual Quality Governance (SQG) framework, which integrates managerial effectiveness, institutional legitimacy, and moral-spiritual responsibility in pesantren governance. This study is limited to three elite pesantren; therefore, its results cannot yet be generalised to all types of pesantren in Indonesia. Consequently, future research is recommended to test the relevance of the SQG framework across various models of Islamic educational institutions using a comparative approach or mixed-methods design to expand its empirical validity and theoretical development